Signaling in Migrating Neurons: From Molecules to Networks - Khodosevich, Konstantin; Monyer, Hannah (Frontiers in Neuroscience, 2011)
During prenatal and postnatal development of the mammalian brain, new neurons are generated by precursor cells that are located in the germinal zones. Subsequently newborn neurons migrate to their destined location in the brain. On the migrational route immature neurons interact via a series of recognition molecules with a plethora of extracellular cues. Stimuli that are conveyed by extracellular cues are translated into complex intracellular signaling networks that eventually enable neuronal migration. In this Focused Review we discuss signaling networks underlying neuronal migration emphasizing molecules and pathways that appear to be neuron-specific.